The dual effector system for exocytosis in mast cells: Obligatory requirement for both Ca2+ and GTP. Issue 5 (May 1987) - Gomperts, B. D.; Cockcroft, S.; Howell, T. W.; Nüsse, O.; Tatham, P. E. R.
Abstract : The secretory process is a coordinated cellular response, initiated by occupation of surface receptors and comprising an ordered sequence of biochemical steps subject to multiple controls. Conceptually we can divide the sequence into two main sections comprising early, receptor-mediated events leading to generation of intracellular second messengers, and later events leading to membrane fusion and exocytosis. With the discovery that occupation of Ca 2+ mobilising receptors leads to activation of polyphosphoinositide phosphodiesterase (PPI-pde) through the mediation of a G-protein (Gp), all the early events can be ascribed to the plasma membrane. Investigation of the exocytotic stage of secretion has been simplified by the use of permeabilised cells in which the composition of the cytosol can be precisely controlled. We have used streptolysin-O, a bacterial cytolysin which generates protein-sized pores in the plasma membrane, to investigate the exocytotic mechanism of rat mast cells. We find that in addition to the activation of PPI-dpe, GTP also acts in concert with Ca 2+ at, or close to, the exocytotic site. Exocytosis can occur after substantial depletion of cytosol lactate dehydrogenase and 3-phosphoglycerate kinase indicating that soluble cytosol proteins are unlikely to play any role. There is no absolute requirement for ATP or phosphorylating nucleotide in exocytosis though when present the effective affinities of the two obligatory effectors (i.e. Ca 2+ and GTP) are substantially enhanced.